The Impact of HR Development and Organizational Roles on Employee Performance via Engagement in MSMEs Indonesia - Lukman Hakim; Sabil Sabil; Amin Setio Lestiningsih; Dwiyatmoko Puji Widodo; Sugiyah Sugiyah; Devy Sofyanty (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze the effects of human resource development (HRD) and organizational roles on employee performance, with employee engagement as a mediating variable in Micro, Small and Medium Enterprises (MSMEs) in Indonesia. HR development and organizational roles are crucial factors in increasing employee productivity and competitiveness. The research method used is a quantitative approach with regression analysis techniques and mediation tests to understand the relationship between variables. Data were collected through a survey of 125 MSME employees in various industrial sectors in Indonesia. The results showed that HR development and organizational roles have a positive and significant effect on employee performance. In addition, employee engagement is shown to play a mediating role that strengthens the relationship between HR development and organizational roles with employee performance. The implications of this study highlight the importance of HR development strategies and improved organizational roles in creating a work environment that supports employee engagement to improve their performance